Diálogo do imponderável: cinco ensaios sobre o objeto psicológico a partir da filosofia da mente - Xavier, César Rey (Universidade Federal de São Carlos, 2008)
It is well known by all those who study psychology that an undisguisable difficulty shows up whenever its object of study is called upon. Of all epistemological problems that a science may face, a fragmented definition of its object is certainly the hardest to deal with. This is the cornerstone of the statute of psychology. No matter what explanation shows up to justify such fragmented state, the fact is that the different research communities, known as schools , don t share the same basic notions to form a concept of what they re studying. We understand basic notions as models that precede the object s own definition. In the lack of a model for the psychological object that is wide enough to place the orbits of these schools around a cohesive axis, each one of them elects their own conception of their object of study, which will be consider as psychology s minor objects . If a science is capable of such diversity within its corpus, to the point of making any attempt of unity of its parts a difficult task, for sure there must be a characteristic that makes it sui generis. Such characteristic may only be understood within the nature of the object itself, whose phenomenology may be qualified as double-faced , sometimes describing physical properties (belonging to the field of the nature sciences ), sometimes circumscribing abstract properties (belonging to the field of the spirit sciences ). That s what we call imponderable , for such versatility, intrinsic to the psychological object, also translates its paradoxical character. Throughout this thesis, it will be demonstrated, based upon this character, the intimate dependency of psychology in respect to mind philosophy, for an epistemological solution of the first goes through the mind-body problem of the latter. Carefully examining certain lines of the works of four great thinkers, namely, R. Descartes, G. Ryle, S. Freud and C. G. Jung, this philosophical problem becomes evident under different expressions, something that, even though there are differences among them, points to a common link, that can also be pointing to a possible wider model to the psychological object, that coincides with what this thesis considers to be psychology s major object . To such a hypothetical model, the following work offers the term hybrid to elucidate it, using, for such, an intertwined historical and epistemological reflection, leading to a phenomenological hermeneutics.
Keywords: Objeto psicológico; Corpo e mente problemas; Fenomenologia; Imponderável; Psychological object; Mind-body problem; Imponderable; Phenomenon; Hybrid; CIENCIAS HUMANAS::FILOSOFIA